The World Jewish Congress during the Holocaust : between activism and restraint - Segev, Zohar (New perspectives on modern Jewish history, 2014)
Main description: Drawing onhitherto neglected materials,Zohar Segev sheds new light on the policy of the World Jewish Congress (WJC) during the Holocaust. Contrary to popular belief, he can show that there was an impressive system of previously unknown rescue efforts. Furthermore, in stark contrast to the Zionist movement, WJC leaders strove to establish a Jewish state and to rehabilitate Diaspora Jewish life, two goals they saw as mutually complementary.